2018
DOI: 10.1016/j.ejmech.2018.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Azulene-based compounds for targeting orexin receptors

Abstract: A library of 70 000 synthetically accessible azulene-based compounds was virtually screened at the OX receptor. Based on the results, a series of azulene derivatives was synthesized and the binding to and activation of both orexin receptor subtypes were assessed. Two most promising binders were determined to have inhibition constants in the 3-9 μM range and two other compounds showed weak OX receptor agonism. Furthermore, three compounds exhibited a concentration-dependent potentiation of the response to orexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…Notably,t he assay cannot discriminate between weak agonists and ago-PAMs (compounds that have both agonist and positive allosteric modulator activities), as the increase of intracellularC a 2 + levels, which is ah allmark of the orexin receptora ctivation, directly potentiates the downstream signaling machinery and thus gives ap ositive signal. [12,21,[27][28][29][30] Compounds 5, 6,a nd 27 potentiated the response to orexin-A on OX 1 receptors by 1.4-, 1.6-, and 1.3-fold, respectively,a t1 0mm ( Figure S1 and Ta ble S1,S upporting Information). Additionally, compounds 10 (OX 1 ), 16 (both receptor subtypes), 19 (OX 2 ), and 24 (OX 1 )s howed aw eak potentiatinge ffect,b ut comparison with their effect on the control ATPr esponse suggested that these are not mediated specifically by orexin receptors (Table S1,S upportingI nformation).…”
Section: Activityassessment Of the Azulene-based Derivativesmentioning
confidence: 92%
See 4 more Smart Citations
“…Notably,t he assay cannot discriminate between weak agonists and ago-PAMs (compounds that have both agonist and positive allosteric modulator activities), as the increase of intracellularC a 2 + levels, which is ah allmark of the orexin receptora ctivation, directly potentiates the downstream signaling machinery and thus gives ap ositive signal. [12,21,[27][28][29][30] Compounds 5, 6,a nd 27 potentiated the response to orexin-A on OX 1 receptors by 1.4-, 1.6-, and 1.3-fold, respectively,a t1 0mm ( Figure S1 and Ta ble S1,S upporting Information). Additionally, compounds 10 (OX 1 ), 16 (both receptor subtypes), 19 (OX 2 ), and 24 (OX 1 )s howed aw eak potentiatinge ffect,b ut comparison with their effect on the control ATPr esponse suggested that these are not mediated specifically by orexin receptors (Table S1,S upportingI nformation).…”
Section: Activityassessment Of the Azulene-based Derivativesmentioning
confidence: 92%
“…The synthesis of the starting materials 4 and 20 was described previously. [12] Ketone derivatives of 4 were obtainedb ya pplying modified Vilsmeier-Haack reactionc onditions (Scheme 1). As the reactions gave only low to moderate yields, the unreacteds tartingm aterial was recovereda nd used in the synthesis of other ketone derivatives.…”
Section: Chemistrymentioning
confidence: 99%
See 3 more Smart Citations